IoT Air Pollution Monitoring System - Mohd Azi, Muhammad Syazwan; M. Yusoff, Zakiah; Khirulanuar, Muhammad Sharul Haikal; Razali, Noor Fadzilah; Markom, Arni Munira (2020)
Air quality must be monitored and kept under control for a better future and a healthy life. Here we propose an air quality as well as an air pollution monitoring system enable us to monitor and control the quality of live air through IoT in specific areas. This system used sensor to constantly detect harmful gases in the air. System also maintains the air level measurement and reports it via IoT to the Blynk application. The sensor interacts with the microcontroller to process the data and transmit through the internet. This allows authorities to monitor and take action against air pollution in various areas. Authorities can also monitor air pollution in the vicinity of school, and hospital. Where the system detects the air quality problem, the authorities are alerted so they can take control measure. The main component of IoT air pollution monitoring system is Arduino Mega 2560 as a microcontroller. The input used is MQ135 sensor and MQ-7 to detect contaminated air. This sensor will place at a higher place to easily detect the pollution air. There are 3 output are LEDs, Wi-Fi module, and LCD display. This probably uses a LED and buzzer as an indicator on this system to show the system is running. The LCD is used to show the air concentration either the safe air or not. If the air is polluted, the system will bring alerts to nearby areas. This Wi-Fi module helps a nearby people to know information about air concentration. This surely can make they feel safe because they can know about current air concentration.